Testing Laser-Structured Antimicrobial Surfaces Under Space Conditions: The Design of the ISS Experiment BIOFILMS - Siems, Katharina; Müller, Daniel W.; Maertens, Laurens; Ahmed, Aisha; Van Houdt, Rob; Mancinelli, Rocco L.; Baur, Sandra; Brix, Kristina; Kautenburger, Ralf; Caplin, Nicol; Krause, Jutta; Demets, Rene; et al. (Frontiers in Space Technologies, 2022)
Maintaining crew health and safety are essential goals for long-term human missions to space. Attaining these goals requires the development of methods and materials for sustaining the crew’s health and safety. Paramount is microbiological monitoring and contamination reduction. Microbial biofilms are a special concern, because they can cause damage to spaceflight equipment and are difficult to eliminate due to their increased resistance to antibiotics and disinfectants. The introduction of antimicrobial surfaces for medical, pharmaceutical and industrial purposes has shown a unique potential for reducing and preventing biofilm formation. This article describes the development process of ESA’s BIOFILMS experiment, which will evaluate biofilm formation on various antimicrobial surfaces under spaceflight conditions. These surfaces will be composed of different metals with and without specified surface texture modifications. Staphylococcus capitis subsp. capitis, Cupriavidus metallidurans and Acinetobacter radioresistens are biofilm forming organisms that have been chosen as model organisms. The BIOFILMS experiment will study the biofilm formation potential of these organisms in microgravity on the International Space Station on inert surfaces (stainless steel AISI 304) as well as antimicrobial active copper (Cu) based metals, that have undergone specific surface modification by Ultrashort Pulsed Direct Laser Interference Patterning (USP-DLIP). Data collected in 1 x g has shown that these surface modifications enhance the antimicrobial activity of Cu based metals. In the scope of this, the interaction between the surfaces and bacteria, which is highly determined by topography and surface chemistry, will be investigated. The data generated will be indispensable for the future selection of antimicrobial materials in support of human- and robotic-associated activities in space exploration.